2019
DOI: 10.1523/jneurosci.0805-19.2019
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of FGF Receptor-1 Suppresses Alcohol Consumption: Role of PI3 Kinase Signaling in Dorsomedial Striatum

Abstract: Excessive alcohol intake leads to mesostriatal neuroadaptations, and to addiction phenotypes. We recently found in rodents that alcohol increases fibroblast growth factor 2 (FGF2) expression in the dorsomedial striatum (DMS), which promotes alcohol consumption. Here, we show that systemic or intra-DMS blockade of the FGF2 receptor, FGF receptor-1 (FGFR1), suppresses alcohol consumption, and that the effects of FGF2-FGFR1 on alcohol drinking are mediated via the phosphoinositide 3 kinase (PI3K) signaling pathwa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(42 citation statements)
references
References 92 publications
8
34
0
Order By: Relevance
“…Similar to what was observed with FGF2, Fgfr1 gene expression was increased in the DMS of mice after 5 weeks of voluntary ethanol consumption using an intermittent access 2 bottlechoice protocol [44]. Treatment with the FGFR1 inhibitor, PD173074 (which also inhibits FGFR3 and FGFR4), via systemic injection in mice or by direct infusion into the DMS of rats decreased ethanol consumption and preference in the intermittent access 2-bottle choice test (Table 1) [44]. PD173074 is not currently clinically approved, but second-generation pan-FGFR antagonists such as AZD4547, BGJ398, LY2874455, and JNJ-42756493 (erdafitinib) that are selective for FGFR over other tyrosine kinases are currently in clinical trials for cancer treatment [119,120].…”
Section: Fgfr and Egfrsupporting
confidence: 78%
See 3 more Smart Citations
“…Similar to what was observed with FGF2, Fgfr1 gene expression was increased in the DMS of mice after 5 weeks of voluntary ethanol consumption using an intermittent access 2 bottlechoice protocol [44]. Treatment with the FGFR1 inhibitor, PD173074 (which also inhibits FGFR3 and FGFR4), via systemic injection in mice or by direct infusion into the DMS of rats decreased ethanol consumption and preference in the intermittent access 2-bottle choice test (Table 1) [44]. PD173074 is not currently clinically approved, but second-generation pan-FGFR antagonists such as AZD4547, BGJ398, LY2874455, and JNJ-42756493 (erdafitinib) that are selective for FGFR over other tyrosine kinases are currently in clinical trials for cancer treatment [119,120].…”
Section: Fgfr and Egfrsupporting
confidence: 78%
“…Evidence that FGFR1 might be involved in AUD was demonstrated by Even-Chen and Barak, who found that 7 days of 2.5 g/kg ethanol injections in mice increased Fgfr1 gene expression in the DS and dorsal hippocampus 24 h after the final injection. Similar to what was observed with FGF2, Fgfr1 gene expression was increased in the DMS of mice after 5 weeks of voluntary ethanol consumption using an intermittent access 2 bottlechoice protocol [44]. Treatment with the FGFR1 inhibitor, PD173074 (which also inhibits FGFR3 and FGFR4), via systemic injection in mice or by direct infusion into the DMS of rats decreased ethanol consumption and preference in the intermittent access 2-bottle choice test (Table 1) [44].…”
Section: Fgfr and Egfrsupporting
confidence: 52%
See 2 more Smart Citations
“…2011 ). Interestingly, recent works also showed that the need for alcohol consumption could be reduced by inhibiting fibroblast growth factor 2 (FGF2) expression via PI3K signalling ( Even-Chen & Barak 2019 ). Early works have demonstrated that activation of PI3K pathway happens via phosphorylation of tyrosine residues in the SH2 domain of p85 ( Yu et al .…”
Section: Discussionmentioning
confidence: 99%